Investigation of the effect of financial performance on company value with corporate social responsibility as a moderating variable in sub-sector industry manufacturing companies listed on the Indonesia stock exchange - Seri Suriani; Ida Ayu Putu Megawati; Nurcahya Hartaty Posumah; Deni Apriansyah; Irwan Moridu (Enrichment : Journal of Management, 2023)
This observe targets to decide the effect of economic overall performance (ROA) on company cost, and to determine whether or not Corporate Social Responsibility (CSR) is capable of moderate the impact of economic overall performance on organization cost in chemical production corporations listed at the Indonesian Stock Exchange. Sampling in studies the use of purposive sampling. The company's monetary file facts taken is the yearly monetary record. The analytical technique used is easy linear regression evaluation for speculation I and a couple of regression evaluation and moderating regression evaluation for hypothesis II. The results of the study the use of easy linear regression analysis display that the tcount value of four.032 with a significance of zero.000 is decrease than α = five% or 0.05, so the outcomes of this look at assist the proposed speculation (H1), this indicates monetary overall performance ( ROA) has a effective impact on firm price. While the evaluation of the moderating variable shows that the R Square fee in the first regression is zero.504 or 50.4%, even as after the second regression equation the R Square fee increases to zero.676 or sixty seven.6%. Thus, it can be concluded that the proposed hypothesis (H2) is time-honored. This indicates that Corporate Social Responsibility moderates the impact of economic performance (ROA) and firm price.